Pemetaan Daerah Rawan Banjir di Kabupaten Padang Pariaman Menggunakan Sistem Informasi Geografis - Syukri, Alfi; Wilis, Ratna (Lembaga Yasin AlSys, 2025)
This research aims to find out: (1) Mapping of flood-prone areas by utilizing geographic information systems. (2) The effect of land use on the surface flow coefficient in Padang Pariaman Regency. This research is descriptive with a quantitative approach. By using data analysis techniques overlap or overlay. The results of this study indicate that (1) the mapping of flood-prone areas in Padang Pariaman Regency shows a classification with 3 classes of flood vulnerability “Very Prone 608.84 (45%) km², covering the Districts of Batang Anai, Batang Gasan, Nan Sabaris, Ulakan Tapakis, and Sungai Limau. Moderately Prone 533.73 (40%) km², covering the sub-districts of Enam Lingkuang, Lubuk Alung, Sintuk Toboh Gadang, 2x11 Enam Lingkuang, Kampuang Dalam, and Sungai Sariak. and Not Prone 207.20 (15%) km²”, covering the sub-districts of 2x11 Kayu Tanam, IV Koto Aur Malintang, Lubuk Alung, Padang Sago, Patamuan, Sungai Garinggiang. (2) Factors that cause flooding through land use using the flow coefficient that land use affects flooding, especially local flooding caused by the amount of surface runoff discharge in Padang Pariaman Regency is greatest in December and March at 48,515 and 48,088 M³/second, while the lowest occurs in June at 16,153 M³/second.